Risk-based inspection (IBR-API RP 580) - Meneses Ramirez, Edgard (2010)
Risk Based (RBI ) inspection is a risk -based prioritization and planning of inspections , mainly in the oil and gas focus. This type of inspection planning analyzes of the probability of failure and the consequences thereof for the purpose of developing the inspection plan . It is related to the asset management based on risk, integrity management based on risk management and risk-based results . It is used to prioritize inspection, usually by means of non-destructive testing (NDT) , the requirements for the major oil rigs, mining centers, refineries and chemical plants worldwide. The results of the inspection plan describes the type and frequency of inspection for the assets of a company are used for industrial piping systems, process piping , structures, and many other types of assets in these sectors. Items with high probability and consequences of failure (ie , high risk ) are given a higher priority for inspection than items with low probability of failure so it has low consequences. This strategy allows a rational investment of inspection resources .